Electrochemical ammonia synthesis catalyzed with a CoFe layered double hydroxide – A new initiative in clean fuel synthesis. (20th March 2020) - Qiao, Lingling; Duan, Guoyi; Zhang, Sheng; Ren, Yuan; Sun, Yanzhi; Tang, Yang; Wan, Pingyu; Pang, Ran; Chen, Yongmei; Russell, Armistead G.; Fan, Maohong
Abstract: Electrochemical ammonia synthesis is regarded as a green, clean, and sustainable technology alternative to the Haber-Bosch process to reduce fossil fuel consumption and greenhouse gas emission. In this research, an earth-abundant CoFe layered double hydroxide was prepared with a simple one-step hydrothermal method and was employed as a promising catalyst for electrochemical ammonia synthesis. The CoFe double hydroxide exhibited excellent catalytic activity with a high generation rate of 1.1 × 10 −9 mol s −1 cm −2 in a single-chamber cell, and a high Faradaic efficiency of 14.18% was obtained when the concentration of protons and electrons was limited in a double-chamber cell. The outstanding catalytic performance of CoFe layered double hydroxide was attributed to the abundant N2 adsorption sites provided by the binder-free three-dimensional nano-structure and the synergy between the Co and Fe atoms in the layer. A microkinetic model of electrochemical ammonia synthesis catalyzed with CoFe layered double hydroxide was proposed, which was consistent with the experimental results. A possible ammonia synthesis mechanism was proposed based on the experiments and theoretical calculations. Graphical abstract: Image 1 Highlights: Electrochemical ammonia synthesis under mild conditions. Electrochemical ammonia synthesis from nitrogen and water. LDHs were used for catalyzing electrochemical NH3 synthesis for the first time. The ammonia generation rate by using CoFe-LDH as catalyst is as high as 1.1 × 10 −9 mol s −1 cm −2 in the single-chamber system. The faradaic efficiency by using CoFe-LDH as catalyst is as high as 14.18% in the double-chamber system.